Avaliação de sistemas de reparo para o problema de abrasão do concreto de superfícies úmidas em usinas hidrelétricas - PINHO, José Rodrigo Santana (2006)
The research field of construction pathology has been steadily growing lately due to natural degradation observed in different structures. In this sense, great attention has been devoted to special concrete structures such as hydroelectric power plants (HPP) because of their complexity and importance, socially as well as economically. One of the pathologies that is most found in these structures is hydraulic abrasion of concrete, which can lead, in extreme cases, structures to complete failure. The objective of this research work is to obtain and analyze test data of various repair materials regarding their resistance to hydraulic abrasion as well as their respective adherence systems. The research was divided into three phases: the purpose of the first phase was to investigate the physical and mechanical characteristics of the repair materials; the objective of the second phase was to analyze the compatibility between the repair material and the substrate through the evaluation of adherence by the slant shear test; Finally, the purpose of the third phase was to provide data about the abrasion resistance of the repair materials through the ASTM C1138 testing method. In the first phase, axial compression tests and consistence tests were perfomed with the concretes and mortars used as deep and superficial repairs at 3, 7 and 28 days. In the second phase, adherence tests were made, at 3 and 28 days, in the adhesive systems, which consisted of polymers and cement based materials. In the last phase, the same repair materials of the first phase were used: cement based mortars and concretes with and without pozolanic addition silica fume and high reactive metakaolin and an epoxy mortar at 3 and 28 days of age. As results, axial compression strengths between 40 to 65 MPa were obtained for the cementitious materials at 3 days of age and between 60 to 80 MPa at 28 days. Meanwhile the epoxy mortars strength was 20 MPa for both ages. The mortars consistency was thixotropic, while the concretes ones were very fluid. Regarding the adherence tests, the surfaces were first scarified, then clean and wet, which provided a condition for the cementitious adhesives to perform much better than the polymeric ones, even for those that were recommended for adhesion in wet substrates. In the abrasion test phase, a new methodology was used to prepare the concrete substrates before the application of the repair materials. The repair that achieved the best results under abrasion was the epoxy mortar. No statistically significant difference was observed between the concretes with and without pozzolanic additions. In general, the mortars wear, especially at 3 days, was larger than the concretes wear, in which the presence of two stages of rate of degradation were clearly verified, due to the abrasion resistance of the coarse aggregates. Therefore, it was possible to identify different stages of abrasion wear for the tested concretes.